2020
DOI: 10.3390/molecules25122728
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evaluation of Artemisia cina Crude CO2 Subcritical Extract after the Removal of Santonin by Means of High Speed Countercurrent Chromatography

Abstract: Artemisia species are highly important due to their economic significance as medicines, fodder and food. Artemisia cina is an endemic species to Kazakhstan. In folk medicine, water extract of A. cina was used in the treatment of bronchial asthma while the alcohol extract has larvicidal and antituberculosis activity. The most common and most extensively studied compound from this species is the terpenoid santonin. The toxicity of this compound occurs at the doses of 60 mg for children and 200 mg for adults caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…A recent investigation demonstrated that naringenin increases locomotor activity and reduces diacylglycerol accumulation [ 2 ]; hesperidin affects the microbial spoilage and antioxidant quality [ 3 ]. A derivate from heptamethoxyflavone induces a brain-derived neurotrophic factor via cAMP by extracellular signal-regulated kinase [ 4 ]; other flavonoids have antiproliferative activities in cancer cell lines [ 5 ]; antinociceptive and anti-inflammatory effect [ 6 ], and activities in Alzheimer’s disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation demonstrated that naringenin increases locomotor activity and reduces diacylglycerol accumulation [ 2 ]; hesperidin affects the microbial spoilage and antioxidant quality [ 3 ]. A derivate from heptamethoxyflavone induces a brain-derived neurotrophic factor via cAMP by extracellular signal-regulated kinase [ 4 ]; other flavonoids have antiproliferative activities in cancer cell lines [ 5 ]; antinociceptive and anti-inflammatory effect [ 6 ], and activities in Alzheimer’s disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, to cure bronchial asthma, a warm water soup of the dried plant is taken orally ( Sakipova et al, 2020 ). Quercetin reported, cause bronchodilation within living and artificial environment.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the spontaneous flora of Kazakhstan, consisting of many endemic and rare species [ 20 , 21 ], can be regarded as a rich source of several, not fully explored medicinal plants with novel potential applications [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Therefore, attempts have been made to introduce them for cultivation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%